(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
More personal, convenient, and cost-effective ways for sellers to engage with consumers are emerging as a result of technological advancements. In recent years, e-commerce has grown at an unprecedented rate. Online shopping has become the norm in the retail sector, but fast-growing supermarket chains like Supermarket and Hypermarket are also making waves. Online shopping is popular among many people. On the other side, shopping in mega and hypermarkets has been popular for a while. Many shoppers still prefer to do their shopping in physical stores, where they can handle the products and get a feel for them before committing to a purchase. Customer loyalty in the modern day is shaped by a company’s capacity to provide quality, reasonable prices, and happiness. Some individuals prefer to just purchase in physical stores, while others like the convenience of internet shopping as well.